Hubungan Antara Rhinitis Alergi Dengan Sinusitis Pada Pemeriksaan Foto Sinus Paranasal di RSUD DR. H. Abdul Moeloek Bandar Lampung Tahun 2019 - Tantri Dwi Kaniya Retno Hapsari; Mardheni Wulandari; Haryadi Haryadi; Salma Restiany Sabilla (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Sinusitis and rhinitis are closely related diseases, especially chronic rhinitis. Allergic rhinitis is an allergic reaction to the nose that exposed to allergens. Sinusitis is an inflammatory disease that occurs in the sinus mucosa caused by inflammation of the nose with symptoms in the form of nasal congestion and pressure in the infected sinus area. Purpose: This study aims to determine whether there is a relationship between Allergic Rhinitis and Sinusitis on Paranasal Sinus Photo Examination at RSUD DR. H. Abdul Moeloek Bandar Lampung in 2019. Research Method: The research method used in this study is a descriptive analytic study with a cross sectional approach because it intends to analyze the influence or relationship in the study. The research design is cross sectional, which is a type of research conducted by collecting data only once at a time. The result: By using the Chi Square test, it shows a p-value = 0.000 which is less than the significance value of 5% (0.05), this shows that there is a significant relationship between allergic rhinitis and sinusitis. From the above analysis, it was found that the OR value = 17.28, which states that patients who experience allergic rhinitis have 17.28 times to experience sinusitis. By using the Chi Square test, it shows a p-value = 0.000 which is less than the significance value of 5% (0.05), this shows that there is a significant relationship between allergic rhinitis and sinusitis. Conclusion: There is a significant relationship between allergic rhinitis and sinusitis on the paranasal sinus photo examination at RSUD DR. H. Abdul Moeloek Bandar Lampung in 2019.